Accuracy of fetal gender determination in maternal plasma at 5 and 6 weeks of pregnancy - Martinhago, Ciro Dresch; de Oliveira, Ricardo Manoel; Tomitao Canas, Maria do Carmo; Vagnini, Laura Diniz; Alcantara Oliveira, Joao Batista; Petersen, Claudia Guillhermino; Franco Junior, Jose Gonçalves [UNESP] (Wiley-Blackwell, 2006)
Objective To assess the viability of the early diagnosis of fetal gender in material plasma before 7 weeks of pregnancy by real-time polymerase chain reaction (real-time PCR), starting at 5 weeks of pregnancy.Method peripheral blood was collected from pregnant women, starting at 5 weeks of gestation. After centrifugation, plasma was separated for fetal DNA extraction. DNA was analyzed by quantitative real-time PCR for two genomic regions, one on the Y chromosome (DYS-14) and the other shared by both sexes (beta-globin), by the TaqMan Minor Groove Binder (MGB) probe assay. The results of the examinations were compared to fetal gender determined after delivery.Results A total of 79 examinations of fetal DNA in maternal plasma were performed for 52 pregnant women. Accuracy according to gestational age was 92.6% (25 of 27 cases) at 5 weeks, and 95.6% (22 of 23 cases) at 6 weeks. These results also demonstrate that fetal DNA is present at low concentrations in maternal plasma at 5 weeks (8.5 genome equivalents (GE)/mL) and 6 weeks (34.1 GE/mL) of pregnancy.Conclusion Quantitative real-time PCR and TaqMan MGB probes specific for the detection of fetal gender in maternal plasma starting at 5 weeks of gestation have good sensitivity and excellent specificity. Copyright (c) 2006 John Wiley & Sons, Ltd.
Keywords: real-time PCR; TaqMan Minor Groove Binder; fetal DNA; maternal plasma; fetal sexing